Production protocols in the current practice of instilling traditional values in Malay kuih - Kamaruzaman, Mohd Yusof; Ab. Karim, Shahrim; Che Ishak, Farah Adibah; Arshad, Mohd Mursyid (Qualitative Research Association of Malaysia, 2023)
Traditional food is unique to every country and can act as one of the catalysts for the nation’s economy, especially through gastronomic tourism activities. However, the qualities of traditional food are now challenged by globalization-imposed modernization innovations. The change in methods and techniques in producing traditional food has altered the traditional values of the delicacies. This study explored the disciplines within the production of traditional Malay kuih that instilled the traditional value in the current practices. A qualitative research design was utilised in this study using in-depth interviews and focus group discussions. There were 21 informants involved in the data collection, out of which 14 were traditional Malay kuih producers, while 7 were loyal consumers, all of whom were within the data saturation point gathered from sessions. All the interview sessions were audio recorded and transcribed verbatim to extract themes for the research question “How can the traditional quality of Malay kuih be reproduced in current practice?” Four themes were discovered where protocols were applied in the production of traditional Malay kuih. The protocols are; using Malay’s conventional cooking techniques, controlling ingredient substitutions in original recipes, controlling technical enhancement in production, and retaining the common flavour of the traditional Malay kuih. These findings not only covered the integrity of traditional methods while adapting to modern technology but also contributed to an in-depth discovery of practices and limitations set upon the production of traditional Malay kuih from the informants’ experiences. Producers of the traditional Malay kuih can then better organize their productions while still conforming to instill traditional values in their products. Consequently, this confers well-identified and true-to-origin tourism products to attract the locals as well as foreign tourists to enjoy the delicacies. With the findings of this study, the specification of the traditional Malay kuih can further be rekindled and expand on possibilities for its resurgence.